Effect of community attitudes on suicide mortality in South Korea: a nationwide ecological study - Hong, Minseok; Kim, Hyesoo; Park, C. Hyung Keun; Lee, Hyunju; Rhee, Sang Jin; Min, Sooyeon; Kim, Min Ji; Yang, Jeong Hun; Song, Yoojin; Son, Kyunghoon; Ahn, Yong Min (Frontiers in Psychiatry, 2024)
Background: Attitudes toward suicide are essential in suicide prevention, as suicide is socio-culturally nuanced. Although the relationship between individual attitudes and suicidal behavior has been extensively studied, the effect of community attitudes—aggregated by region—on suicide mortality remains ambiguous. This study explored the association between community attitudes and real-world suicide mortality. Methods: Data on attitudes toward suicide from the 2018 Korea National Suicide Survey (N=1500) and individual mortality data from the MicroData Integrated System were obtained. Confirmatory factor analysis supported a factor structure with three factors: "Permissiveness," "Unjustified behavior," and "Readiness to help/Preventability." Thirty regional units in South Korea aggregated the data for ecological analysis. We used negative binomial models to examine the association at the regional level, and stratified analysis by gender and age group was conducted. Results: "Permissiveness" was associated with reduced suicide rates in a univariate model (P<0.001). Adjusting for gender, age, and additional sociodemographics did not alter the association. Additionally, this relationship was observed in males and individuals under 60 years of age after stratification. However, "Unjustified Behavior" and "Readiness to help/Preventability " exhibited no significant association with suicide in any model or stratum. Conclusion: The observed inverse association between permissive community attitudes and suicide contradicts the findings of previous research that links permissive individual attitudes to increased suicidal behavior. Our findings suggest that attitudes may operate differently at the individual and group levels. Although the cross-sectional design and single-country focus of this study warrant further investigation, our findings indicate that attitudes are significant contextual factors in the process of suicide, which could lead to novel approaches in suicide prevention.